Variable Mass of the Test Particle in the Collinear 4-Body System with Triaxial Primaries - Abdullah Abdullah; Rabah Kellil (Iranian Journal of Astronomy and Astrophysics)
The mass variation effect of the test particle is studied in the collinear restricted four-body configuration with the assumption that the shapes of the three primary bodies are triaxial. It is assumed that these three primary bodies are placed in consecutive order on the abscissa axis and their axes are always parallel to the synodic ones. We also consider that the central body have solar radiation effect and whole the system is affected by Coriolis as well as centrifugal forces. Under these assumptions and using Jeans’ law, the equations of motion and quasi-Jacobian integral are determined. And hence the locations of parking points, Poincaré surfaces of section, surfaces with projection and basins of attractions are illustrated for the various values of the variation parameters .$μ, φ_1 , φ_2 ,T_{11} , T_{21} , T_{31} , T_{12} , T_{22} , T_{32} , T_{13} , T_{23} , T_{33}$. Further-more the stability of the parking points are examined in the in-plane as well as in the out-of-plane.